Short and long-term repercussions of the experimental diabetes in embryofetal development - Bueno, Aline [UNESP]; Sinzato, Yuri Karen [UNESP]; Sudano, Mateus Jose [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Wiley-Blackwell, 2014)
BackgroundDiabetic pregnancy have increased rates of congenital malformation and neonatal mortality. In vitro studies suggest hyperglycemia associated with diabetes impair embryogenesis but in vivo investigations on maternal hyperglycemic insult and early embryo development are scarce. We evaluated the embryofetal development on experimental diabetes models to assess whether hyperglycemia at preimplantation period impairs the progression of pregnancy.MethodsDifferent hyperglycemic intensities were obtained by two experimental diabetes models. Female Sprague Dawley rats received streptozotocin at birth (mild diabetes) or at day 90 of life (severe diabetes). For both diabetic groups hyperglycemia was confirmed 5 days after diabetes induction and the mating was performed around 100 day of life. For preimplantation analysis, embryos were recovered at D4 of pregnancy. Another group of animals was submitted to laparotomy at D21 to assess contents of the uterus and fetal viability.ResultsMild (i) and Severe (ii) diabetes modified the early development. Degenerating embryos percentage was higher compared to control (11%) (i) 30.7%, (ii) 37.3%. Cell number mean dropped according to hyperglycemic intensity (control 30.57, (i) 21.42, (ii) 13.42). Pre and post-implantation loss rates were higher in diabetic groups. The fetal viability also decreased from 96% in the control group to (i) 78.7% and (ii) 80.6%.ConclusionOur results show that during diabetic pregnancy, preimplantation embryos present decreased cell number due to higher apoptosis rates, which are dependent of the hyperglycemic intensity. Moreover, fetal viability was also decreased suggesting that the quality of these embryos at long-term may be questioned. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: diabetes; pregnancy; preimplantation embryo; embryofetal development; apoptosis; rat